The Aftermath of partition in South Asia - Tan, Tai Young; Kudaisya, Gyanesh (London Routledge)
The Aftermath of partition in South Asia draws upon new theoretical insights of data to reappraise partition historically in the lights of its long aftermath. It uses a comparative approach by viewing South Asia in its totality, rather than looking at it
Keywords: India-History-Partition, 1947; India-History-1947; Pakistan-History